EVALUASI INVESTASI PEMBANGUNAN TAMAN SAFARI DI KABUPATEN GIANYAR - Nadiasa, Mayun; Diana, Maha; Wenten, Sukada (Jurnal Ilmiah Teknik Sipil, 2012)
Evaluation is an assessment of an object; in this case it is the national attractions, ranging from operations to current conditions. The evaluation aims to determine how far the tourist object proceeds financially, so there should be monitoring of costs and revenues. The object of this study is the Safari Park which is initiated by PT. Taman Safari Indonesia and has been operationalized partly. The purpose of this evaluation is to determine the investment condition of Safari Park development which is located on Bypass road of Prof. Dr. Ida Bagus Mantra. The investment parameters are the Net Present Value (NPV) and Benefit Cost Ratio (BCR). Financial values used in the study is based on incurred costs and currently operational costs, while profits are projected based on the number of tourists arrival from opening until now using the linear regression method. The number of tourist arrivals showed an increase in visits since opening until now. This evaluation results in Net Present Value (NPV) of Rp102.220.288.002, 35 and the Benefit Cost Ratio (BCR) value of 2.254. The results of sensitivity analysis with the possibility of all components of revenue decreased by 10% and costs increased by 10% gave NPV of Rp49.162.950.085, 32 and BCR value of 1.600, so this investment is concluded feasible.
Keywords: Investment evaluation, financial aspect.